The Waters of Sexual Exploitation: Understanding the World of Sexually Exploited Youth - Rocke, Cathy; MacKenzie, Laurie; Keast-Wiatrowski, Bram (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2017)
The sexual exploitation of youth is a complex and multidimensional social problem. Understanding the antecedents and factors that entrap youth into the world of sexual exploitation is imperative for effective interventions. This article presents a visual entitled the Waters of Sexual Exploitation that is used as a training tool for social service personnel to understand the world of sexually exploited youth. The visual was developed through an extensive review of the literature as well as in consultation with the Sexually Exploited Youth Training Committee with a specific focus on the overrepresentation of Aboriginal youth who are sexually exploited. The Waters of Sexual Exploitation visual helps to capture the complex relationships that develop between sexually exploited youth, the people that exploit the youth, and the helpers working with youth exiting this world. The visual is enhanced by the inclusion of the lived experience of a survivor of this world.